Study of the influence of σ factors on the kinetics of RNA production - Ferreira, Cristiana Isabel Martins (2015)
Gene expression dynamics inEscherichia coliis controlled at the transcription initiation stage, whichbeginswhen an RNA polymerase holoenzyme, composed of RNA polymerase core enzyme and the σ factor, recognizes the promoter sequence of a gene. Under different conditions, different σ factors are used. Also,some promoters require a specific σ factor, while others haveless specificity. The intracellular levels of σ factors vary between σ factorsand with the cell growth phase.It is still unknown whether different σ factors will lead to differing kinetics of transcription initiation, thereby,in this study it will be characterized the dynamicsof this processby different σ factors, under optimal growth conditionsandunder the control of either of twopromoters, PtetAandPBAD, during the exponential and stationary growth phases. Mutant cells,lacking σ54 or σ38were used and the dynamics of transcription initiation was compared with wild-type cells, for each of the two promoters and during each of the two growth phases. For this, RNA molecules are detected as soon as they are producedin each cell, using an MS2-GFP tagging method,and the distribution of time intervals between consecutive RNA productions are obtainedin each condition.From the results obtained it is concluded that: PtetAis not affected by the σ factors’ populationcompositionduring the two growth cellular phases studied, while PBADit is;the dynamics of transcription initiation is affected by the promoter used; there are 3 rate-limiting steps in transcription initiation under control of the two promoters for the 3 strains during the phases analyzed; the distribution of the intervals are not exponential-like; RNA production is sub-Poissonian; the results of the model developed are in agreement with the observations from in vivomeasurements under control of PtetA,while for PBAD there are some differences.